Path Dependent Battery Degradation Dataset Part 3 - Raj, T (University of Oxford, 2021)
Batteries experience two aging modes: calendar aging at rest and cyclic aging during the passage of current. Existing empirical aging models treat these as independent, but degradation may be sensitive to their order and periodicity – a phenomenon that has been called ‘path dependence’.